The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1999
DOI: 10.1046/j.1469-8137.1999.00331.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and regulation of reduction‐based iron uptake in plants

Abstract: Despite the usually high abundance of iron (Fe) in soils, the low solubility of Fe-bearing minerals restricts the available Fe pools in most aerobic soils to levels that are far below those required for microbial or plant growth. To acquire the necessary amounts of Fe from the environment, organisms have evolved mechanisms that enhance the solubility and dissolution rate of Fe() oxyhydroxides prevailing in aerobic soils. Chemically, these mechanisms are based on weakening of the Fe$O bond by reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
189
0
8

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 352 publications
(204 citation statements)
references
References 301 publications
4
189
0
8
Order By: Relevance
“…In many plant species, Fe deficiency also has a marked stimulatory effect on root hair production (Schmidt, 1999). This response is seen in dicots and in non-grass monocot species as part of a series of physiological and developmental adaptations that help to mobilise Fe in the soil (known as strategy I).…”
Section: Root Hair Length and Densitymentioning
confidence: 99%
See 3 more Smart Citations
“…In many plant species, Fe deficiency also has a marked stimulatory effect on root hair production (Schmidt, 1999). This response is seen in dicots and in non-grass monocot species as part of a series of physiological and developmental adaptations that help to mobilise Fe in the soil (known as strategy I).…”
Section: Root Hair Length and Densitymentioning
confidence: 99%
“…This response is seen in dicots and in non-grass monocot species as part of a series of physiological and developmental adaptations that help to mobilise Fe in the soil (known as strategy I). Roots of the Poaceae (grasses) use a different strategy involving the secretion of phytosiderophores and subsequent uptake of the Fe(III)-phytosiderophore complex (strategy II) (Schmidt, 1999). Fe deficiency substantially increased both the length and number of root hairs in Arabidopsis, the response being seen within 24 h of transferring the seedlings to -Fe medium (Moog et al, 1995).…”
Section: Root Hair Length and Densitymentioning
confidence: 99%
See 2 more Smart Citations
“…For example, several studies have shown the key role of organic acids in affecting plant tolerance to aluminum (Pellet et al 1995;Ma et al 2001). The role of organic acids in mediating the uptake of Fe 3+ was ascribed to ferric reductase activity and the presence of cation channels (Schmidt 1999). Compared to other metals, limited information exists on the interactions between organic acids and Pb at or near the soil-root interface, and the resultant processes of Pb uptake by plant roots.…”
Section: Introductionmentioning
confidence: 99%